Ternary Organic Solar Cells by Small Amount of Efficient Light Absorption Polymer PSEHTT as Third Component Materials - Han Zhang; Songrui Jia; Zhiyong Liu; Zheng Chen (Molecules, 2023)
We prepared ternary organic solar cells (OSCs) by incorporating the medium wavelength absorption polymer PSEHTT into the PM6:L8-BO binary system. The power conversion efficiency (PCE) is improved from 15.83% to 16.66%. Although the fill factor (FF) is slightly reduced, the short-circuit current density (JSC) and open-circuit voltage (VOC) are significantly increased at the same time. A small amount of PSEHTT has a broad absorption spectrum in the short wavelength region and has good compatibility with PM6, which is conducive to fine-tuning the photon collection and improving the JSC. In addition, the highest occupied molecular orbital (HOMO) energy level of PSEHTT is deeper than that of PM6, which broadens the optical bandgap. This study provides an effective method to fabricate high-performance ternary OSCs by using a lower concentration of PSEHTT with PM6 as a hybrid donor material, which ensures a better surface and bulk morphology, improves photon collection, and broadens the optical bandgap.